The role of the pedunculopontine region in basal-ganglia mechanisms of akinesia. - Munro-Davies, L; Winter, J; Aziz, T; Stein, J (1999)
The akinesia of Parkinsonism is relieved by pallidotomy and subthalamic nucleotomy, but not by thalamotomy. Therefore, this disabling symptom probably depends upon connections other than the pallidalthalamocortical tracts, possibly efferents of the medial pallidum descending to the upper brainstem. We have previously demonstrated akinesia in the normal monkey following radiofrequency lesioning in the region of the pedunculopontine nucleus (PPN), one of the primary targets for descending pallidal outflow. Here, we confirm that selectively destroying neurones in the PPN area, whilst sparing fibres of passage, results in an akinetic state in normal macaques.